Occurrence of Acartia tonsa Dana in the Black Sea. Was it introduced from the Mediterranean? - GUBANOVA, A. (Mediterranean Marine Science, 2000)
It was reported for the first time that Acartia tonsa was present in the Black Sea as early as in 1976. A.tonsa was found in the Mediterranean Sea in 1985. So, this copepod was initially introduced to the Black Sea and did not invade here from the Mediterranean. Probably A.tonsa was transferred to the Black Sea with ship's ballast water from some other region of the World Ocean. Differences in seasonal dynamics and size structure of A.clausi and A.tonsa in the Bay of Sevastopol in 1976 are discussed.